2020
DOI: 10.1590/0001-3765202020190449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in 3-to-10-year-old children: assessment of different cut-off criteria WHO-IOTF

Abstract: This study compares the prevalence of overweight and obesity between WHO/ IOTF criteria. A total of 17,277 Portuguese children aged 3-10 years old were analysed. The prevalences of overweight-obesity were higher at WHO classifi cation (19.8%-20.7%) than at IOTF classifi cation (8.2%-16.1%), (p<0.001). Agreement between the criteria were substantial for overweight (Kappa= 0.67, p<0.001) and moderate for obesity (Kappa= 0.47, p<0.001). The prevalences ratio for inequality between criteria were greater for boys t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
2
0
1
Order By: Relevance
“…Our study found a higher prevalence of values based on the WHO curves compared to the IOTF cut-off points. This was also evidenced in other studies (Gama et al, 2020;Kêkê et al, 2015;Shields & Tremblay, 2010;Valerio et al, 2017) and is possibly related to lower WHO cut-off points, resulting from different methodologies used for the development of both references (Cole & Lobstein, 2012). Some studies indicate moderate to significant agreement between the two criteria, varying according to age and sex (Gama et al, 2020;Kêkê et al, 2015;Valerio et al, 2017), suggesting the WHO curves have greater sensitivity but lower specificity than the IOTF cut-off points to detect overweight and obesity among children and adolescents (Cole & Lobstein, 2012), thus corroborating the importance of using both criteria on epidemiological studies.…”
Section: Discussionsupporting
confidence: 88%
“…Our study found a higher prevalence of values based on the WHO curves compared to the IOTF cut-off points. This was also evidenced in other studies (Gama et al, 2020;Kêkê et al, 2015;Shields & Tremblay, 2010;Valerio et al, 2017) and is possibly related to lower WHO cut-off points, resulting from different methodologies used for the development of both references (Cole & Lobstein, 2012). Some studies indicate moderate to significant agreement between the two criteria, varying according to age and sex (Gama et al, 2020;Kêkê et al, 2015;Valerio et al, 2017), suggesting the WHO curves have greater sensitivity but lower specificity than the IOTF cut-off points to detect overweight and obesity among children and adolescents (Cole & Lobstein, 2012), thus corroborating the importance of using both criteria on epidemiological studies.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with IOTF, WHO both underestimates the proportion of thinness and overestimates the prevalence of overweight (including obesity). Our results agree with previous studies, showing a higher prevalence of overweight and obesity among children when using WHO than when using IOTF [3,[8][9][10][11][12][13][14][15][16][17][18][19]. Possible explanations for the difference between IOTF and WHO lie in the different populations, time periods, and methodologies studied, all of which affect the cutoff values [36].…”
Section: Agreement Between Reference Systemssupporting
confidence: 90%
“…In general, a higher prevalence of overweight and obesity has been observed using WHO rather than IOTF reference values in children from various countries across Europe [8][9][10][11][12][13][14][15][16], North America and Asia [3], South America [17,18], and Africa [19]. Yet, opposing findings were reported in two Iranian studies [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…WHO and CDC developed in 2002 the Growth Charts for the United States and this material would henceforth be incorporated into most national guidelines for the assessment of child health and development and the growth screening [ 88 ]. The International Obesity Task Force (IOTF), as part of the International Association for the Study of Obesity (IASO), aiming to the prevention of obesity, developed new cut-offs for defining overweight and obesity, which are used in several countries [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%